Bloggers participation on political issues : main content discussed by Anwaribrahimblog.com and sloone.wordpress.com. - Omar, Siti Zobidah; Tamam, Ezhar; See, Silk Inn (UKM and IPPTAR, 2012)
This article discuss on blloggers participation on political issues, particularly looking at Anwaribrahim blog and Slone blog.